The Influence of Human Resource on Employee Performance and Organizational Commitment in the Road Transport Sector: A Study of Riau Province Transportation Service - Fadhil, Muhammad; Effendi, Zulham (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2024)
This research aims to assess the performance of Civil Servants within the Road Transport Sector of the Riau Province Transportation Service in fulfilling their duties and supporting Organizational Commitment. Employing a qualitative approach, the study involves direct observation and in-depth analysis of existing phenomena using a descriptive method. Key findings include: 1) Civil Servants' performance is generally rated as satisfactory, but falls short in optimizing adherence to Riau Governor Regulation Number 61 of 2021 due to issues such as low work discipline, inadequate competence in task completion, and ineffective inter-employee communication; 2) Competency among Civil Servants is hindered by low engagement in technical training initiatives; 3) Organizational Commitment is notably low, reflecting insufficient awareness of the significance of their roles. Additionally, suboptimal work motivation and inadequate working conditions are evident. Furthermore, the relationship between leadership and staff is characterized by inadequate guidance and motivation, posing challenges to achieving the objectives of the Road Transport Sector of the Riau Province Transportation Service.